A student's English grammar : workbook - Chalker, Sylvia. (Giao thông vận tải, 2003)
The English language. A general framework. Verbs and auxiliaries. The semantics of the verb phrase. Nouns and determiners. Pronouns. Adjectives and adverbs. The semantics and grammar of adverbials. Preposition and prepositional phrases. The simple sentence. Sentence types and discourse funtions. Pro-forms and ellipsis....